EPISTEMOLOGI ILMU-ILMU TASAWUF - Ahmad, Ahmad (Jurnal Ilmiah Ilmu Ushuluddin, 2015)
As all religions have their mysticism, Islamic mysticism is well known as Sufism. In its development, many schools ofSufism appeared and they had been influenced by several religions and beliefs around such as Christian, Buddhism,Hinduism, Gnotisism, etc. This article tends to tell about Islamic Mysticism and its epistemology. It will be discussedabout the definition of Sufism, its schools, its objects, and ways to get it. The writing classified kinds of IslamicMysticism too into three types, Tasawuf Akhlaki, Tasawuf Amali, and Tasawuf Falsafi. Each type has thecertain character. In the end, it will be explained how to know the validity of Sufism.